Jesus according to the New Testament - Dunn, James D. G. (Eerdmans Publishing Co, 2019)
Jesus according to Jesus -- Jesus according to Mark, Matthew, and Luke -- Jesus according to John -- Jesus according to Acts -- Jesus according to Paul: part 1 -- Jesus according to Paul: part 2 -- Jesus according to Hebrews -- Jesus according to James, Peter, John, and Jude -- Jesus according to Revelation